KEPENTINGAN INDONESIA MELAKUKAN KERJASAMA MILITER DENGAN KOREA SELATAN DALAM PENGEMBANGAN PESAWAT TEMPUR KFX/IFX - Gilang Ibnu Afiff; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine the bilateral cooperation agreement between Indonesia and South Korea in developing a fighter aircraft KFX / IFX, factors affecting Indonesia want to follow this agreement, as well as the resulting impact of this agreement on the defense system of the Indonesian state.In order to achieve the objectives of the study, qualitative research method was used. Through this qualitative research method, this study uses literature review or library research which came from books, journals, documents, and various sources from the internet.Basically factors affecting Indonesia to cooperate with South Korea due to meet each other's needs and achieve national interests of Indonesia and South Korea alone. In order to meet the needs of state and national security interests by producing alutista that will strengthen the country's defense.It is concluded that Indonesia implement the cooperation with South Korea is a form of security interests and welfare of the country for Indonesia. With the cooperation of Indonesia to strengthen this country's defense through the air alutista and also will master manufacturing technology fighter aircraft independently.Keywords: Military cooperation, KFX/IFX, National Defense